2020
DOI: 10.3390/insects11040252
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Effects of Pesticides on European Foulbrood in Honeybee Larvae

Abstract: Neonicotinoid and fungicide exposure has been linked to immunosuppression and increased susceptibility to disease in honeybees (Apis mellifera). European foulbrood, caused by the bacterium Melissococcus plutonius, is a disease of honeybee larvae which causes economic hardship for commercial beekeepers, in particular those whose colonies pollinate blueberries. We report for the first time in Canada, an atypical variant of M. plutonius isolated from a blueberry-pollinating colony. With this isolate, we used an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(34 citation statements)
references
References 50 publications
(76 reference statements)
1
33
0
Order By: Relevance
“…Full-size DOI: 10.7717/peerj.11634/fig- 6 Explanations for the EFB phenomenon in blueberries include: a nutritional deficiency with blueberry pollen (Girard, Chagnon & Fournier, 2012), low surrounding floral diversity (Colwell et al, 2017), poor weather conditions during the pollination period (Tuell & Isaacs, 2010), pesticide use (Wood et al, 2020), and the alkalinity of the pollen itself (Wardell, 1983), but so far none have been isolated as the sole or primary determinant. While our study determined the presence and prevalence of EFB in a recommended stocking rate, our approach was descriptive and, as such, unable to test the contention of beekeepers that the disease is more severe at a higher stocking rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Full-size DOI: 10.7717/peerj.11634/fig- 6 Explanations for the EFB phenomenon in blueberries include: a nutritional deficiency with blueberry pollen (Girard, Chagnon & Fournier, 2012), low surrounding floral diversity (Colwell et al, 2017), poor weather conditions during the pollination period (Tuell & Isaacs, 2010), pesticide use (Wood et al, 2020), and the alkalinity of the pollen itself (Wardell, 1983), but so far none have been isolated as the sole or primary determinant. While our study determined the presence and prevalence of EFB in a recommended stocking rate, our approach was descriptive and, as such, unable to test the contention of beekeepers that the disease is more severe at a higher stocking rate.…”
Section: Discussionmentioning
confidence: 99%
“…Field diagnosis of the brood diseases was performed by an experienced honey bee pathologist (A. Melathopoulos). EFB was confirmed using molecular techniques described by Wood et al (2020). Briefly, whenever EFB larvae were identified in an apiary on a given survey date, a minimum of three EFB-diseased larvae were collected using a sterile swab, crushed and stored at −20 • C after returning to the lab at the end of the day.…”
Section: Colony Diseasesmentioning
confidence: 99%
“…Prophylactic treatment of EFB in honey bees in north America is prohibited 4 . Thus, our experimental design considered both metaphylaxis (concurrent infection and treatment) and therapeutic (treatment after infection) antimicrobial interventions of larvae infected with a previously described isolate from British Columbia named M. plutonius 2019BC1 24 . The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of the three antibiotics against M. plutonius 2019BC1 were determined and antibiotic concentrations within and above the range of environmental exposures were evaluated for their ability to protect against EFB and harm honey bee larvae in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…Outcomes vary widely within affected apiaries with some colonies succumbing to disease while others appear completely asymptomatic ( Forsgren et al 2005 , Belloy et al 2007 , Roetschi et al 2008 , Budge et al 2010 ). Outside factors are thought to play an important role in colony outcome after EFB infection, including concurrent stressors related to food, weather, and brood nest growth ( Bailey 1961 , Forsgren 2010 ); overall bacterial loads ( Budge et al 2010 ); specific co-infections ( Erban et al 2017 , Lewkowski and Erler 2019 ); pesticide exposure ( Wood et al 2020 ); or differences in microbiota ( Erban et al 2017 , Floyd et al 2020 ). Some of this variability in virulence and colony outcome may be due to the presence of secondary bacterial pathogens, including Paenibacillus alvei, Enterococcus faecalis, Brevibacillus laterosporus, or Achromobacter eurydice ( Bailey 1957 , Forsgren 2010 , Erler et al 2018 ).…”
mentioning
confidence: 99%
“…Unlike typical strains, atypical strains were shown to be non-fastidious, able to grow in aerobic conditions and on media without potassium salt supplementation. These strains were initially suspected to be restricted to Japan ( Takamatsu et al 2012 ), but have since proven to be widespread ( de León-Door et al 2018 ): to date, atypical strains have additionally been reported in England and Wales, Brazil, Netherlands, United States ( Haynes et al 2013 ), Mexico ( de León-Door et al 2018 ), and Canada ( Woods et al 2020 ). Laboratory testing with the lateral flow device in Japan showed that the device worked as expected with typical strains but responded only weakly to extracts from larvae infected with atypical M. plutonius ( Takamatsu et al 2012 ).…”
mentioning
confidence: 99%